Psychopathy, threat, and polygraph test accuracy. - Patrick, Christopher J.; Iacono, William G. (Journal of Applied Psychology, 1989)
The accuracy of the control question polygraph test with psychopaths was evaluated within a realistically threatening context. Subjects were 24 psychopathic and 24 nonpsychopathic male prison inmates. Within each diagnostic group, equal numbers ofguilty and subjects were tested by experienced professional polygraphers regarding their involvement in a mock theft by using standard control question procedures. A group contingency threat was devised in which subjects believed that their personal performance could decide benefits or penalties for the sample as a whole. Guilty psychopaths were detected just as easily as guilty nonpsychopaths, and the majority of guilty subjects (87%, excluding inconclusives) were correctly identified. However, innocent subjects were identified with only 56% accuracy, and an analysis of false positive errors suggested that the subjective impact of the threat was a critical factor in these outcomes.